A Review of the Phytochemistry, Traditional Uses and Biological Activities of the Essential Oils of Genus Teucrium - Candela, Rossella Gagliano; Rosselli, Sergio; Bruno, Maurizio; Fontana, Gianfranco (Planta Medica, 2020)
The genus Teucrium is a large and polymorphic genus of the Lamiaceae family distributed in mild climate zones, particularly in the Mediterranean basin and Central Asia. Studies of nonvolatile constituents of Teucrium species showed that they are a rich source of neo-clerodane diterpenoids, considered as chemotaxonomic markers of the genus. In addition to the nonvolatile metabolites, there has been a large interest in the essential oils of this genus. In this review, a complete survey of the chemical composition and biological properties of the essential oils isolated from Teucrium taxa is provided. In traditional medicine, since ancient times, species of this genus have been widely implemented for their biological properties, including antimicrobial, anti-inflammatory, antispasmodic, insecticidal, anti-malaria, etc. Therefore, a complete review of all of the traditional uses of Teucrium taxa are also reported.
Keywords: Teucrium; Lamiaceae; ethnopharmacology; essential oil; biological properties